Phenotype and Conditioning Medium on Umbilical Cord-Mesenchymal Stem Cell (UC-MSC) - Kusnanto, Paulus; Purwanto, Bambang; Wasita, Brian; Widyaningsih, Vitri (The Indonesian Society for Digestive Endoscopy, 2023)
Stem cells are unspecialized cells that differentiate into more specialized cells for various tissues in the human body. Stem cells have the characteristics and ability to become themselves by performing various mitoses and differentiating different cells. Stem cells also have great potential for tissue regeneration. Detection and isolation of specific cells is very important in understanding biological processes such as development, aging, regeneration, and cell pathogenesis. Therefore, stem cells are present as an invaluable therapeutic option. Before stem cells can be applied, it is important to know the characteristics of the specific function cells or phenotypic markers. Isolation and characteristics of stem cells on culture morphology or immunotaining on specific markers. Immunohistochemistry can provide a general description of the expression of markers in a cell under certain conditions. Surface markers are the basis for identifying the characteristics and isolation of stem cells. The basic characteristics of stem cells are one that influences the outcome of the therapy to be carried out. The presence of marker cell surface expressions can also be a differentiator in searching for the origin of the stem cells used6. MSC culture method was performed with DMEM + 5% HPL. UC-MSCs with phenotype differentiation were found to be CD73+, CD90+, CD105+, Lin- while the parameters found were IL-6, SDF-1, BDNF, FGF, NGF, IL-12p70, IL-23, IL-18, IL-10 , VEGF, EGF, IL-17A, IFN-, IL-1β, PDGF, MCP-1.The results obtained are in accordance with the standard content of UC-MSC cells which can be continued as cell research.